VARIATIONS IN MORPHOMETRIC TRAITS OF THE INVASIVE ASIAN BLACK TIGER SHRIMP, PENAEUS MONODON (FABRICIUS, 1798) IN THE COASTAL WATERS OF NIGERIA - Nwafili, S. A; Francis, A.; Chukunda, S. N (Nigerian Journal of Fisheries, 2018)
The present study aimed to assess the morphological variations of the invasive Asian tiger shrimp, Penaeus monodon along the coastal waters of Nigeria. A total of 120 individuals were obtained from four locations (New Calabar River, Andoni River System, Apapa Creek, and Ibeno Beach), from February to October 2019. A total of 14 morphometric traits were measured on each individual. The morphometric traits were subjected to Principal Component Analysis using morphometric parameters to identify intra-specific morphological variation. P. monodon exhibited high levels of morphometric variation and the PCA grouped the populations into at least two clusters. It is concluded that environmental differences along the coastal waters and the possibility of multiple pathways of invasion may account for the variations. There is a need to complement the result with DNA analysis.